Laminate, display, method of producing laminate
Patent Information
- Application Number
- JP2023125367
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-01
- Publication Date
- 2025-02-14
AI Technical Summary
【0017】 高輝度、かつ、長時間の連続点灯でも不灯が発生しない、信頼性の高いマイクロLEDディスプレイ、その製造に有用な積層体、および積層体の製造方法を提供できる。
Smart Images

Figure 2025021577000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a laminate, a display, and a method for producing the laminate. [Background technology]
[0002] In recent years, with the development of information terminal devices such as smartphones and tablets, and the increasing resolution of flat panel displays such as televisions, the demand for higher performance displays is increasing. Among these, micro LED displays that use micro-sized light-emitting diodes (LEDs) have attracted attention as a high-performance display. These displays use tiny LEDs (micro LEDs) measuring tens of micrometers or less as a light source to display images, and have a variety of excellent characteristics such as high contrast and low power consumption.
[0003] In this micro LED display, it is necessary to arrange a patterned cured film (partition wall) that separates the light source and has a size corresponding to the micro LED that is the light source. As a method for forming a patterned cured film, photolithography using a pattern mask is well known. In addition, when the LED is small, the light emitted from the LED is mainly radiated in the direction of the side of the chip, so a technology is known in which a reflective white partition wall material is formed on the side of the micro LED in order to efficiently extract the light (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2023-54046 Summary of the Invention [Problem to be solved by the invention]
[0005] However, in micro LED displays, it is necessary to bond the tiny electrodes of the LED to a conductive layer in order to pass electricity through the micro LED to emit light, but because the bonding area is small, connection failures are likely to occur, and there was an issue that light failures tend to occur easily during reliability tests for continuous lighting. This tendency is particularly likely to occur when a partition wall with reflective properties is formed, making it difficult to achieve both high-efficiency light extraction from the micro LED and reliability.
[0006] Therefore, an object of the present invention is to provide a highly reliable micro LED display that is high brightness and unlikely to fail even when continuously lit for a long period of time, a laminate that can be used in the manufacture of the same, and a method for manufacturing the laminate. [Means for solving the problem]
[0007] In order to solve the above problems, the laminate of the present invention has the following configuration. The laminate has a support, a conductive layer, a plurality of light-emitting diodes arranged two-dimensionally, a first organic layer, and a second organic layer, the first organic layer and the second organic layer being in contact with each other, the first organic layer containing (A) a white pigment, and (B) a siloxane resin containing at least 10 to 90 mol % in total of a repeating unit represented by the following general formula (1), and the second organic layer is a transparent layer that is substantially free of siloxane resin.
[0008] [ka]
[0009] (R 1 represents an aryl group having 6 to 18 carbon atoms or an aryl group having 6 to 18 carbon atoms in which all or a portion of the hydrogen atoms have been substituted. In the laminate of the present invention, the second organic layer preferably contains any one of an acrylic resin, a cardo resin, a polyimide resin, and a PBO resin, or a mixture thereof.
[0010] In the laminate of the present invention, the light emitting diode preferably has a thickness of 1 to 20 μm.
[0011] In the laminate of the present invention, the first organic layer preferably has a thickness of 1 to 20 μm.
[0012] In the laminate of the present invention, the conductive layer is preferably a metal layer and / or a metal oxide layer.
[0013] The display of the present invention has the following configuration: That is, the display has the laminate.
[0014] The method for producing a laminate of the present invention has the following configuration. A method for manufacturing a laminate having a support, a conductive layer, a plurality of light-emitting diodes arranged two-dimensionally, a first organic layer, and a second organic layer, the method comprising the steps of: (I) applying a first photosensitive resin composition to form a first coating film; (II) exposing and developing the first coating; (III) a step of heating the first coating film after the development to form a first organic layer; (IV) applying a second photosensitive resin composition onto the first organic layer to form a second coating film; (V) exposing and developing the second coating; and (VI) heating the developed second coating film to form a second organic layer; Including, the first photosensitive resin composition organic layer contains (A) a white pigment, and (B) a siloxane resin containing a total of 10 to 90 mol % of a repeating unit represented by at least the following general formula (1), and the second photosensitive resin composition is a resin composition for forming a transparent layer that is substantially free of siloxane resin.
[0015] [ka]
[0016] (R 1 represents an aryl group having 6 to 18 carbon atoms or an aryl group having 6 to 18 carbon atoms in which all or a portion of the hydrogen atoms have been substituted. Effect of the Invention
[0017] It is possible to provide a highly reliable micro LED display that is high-brightness and does not fail to light even when continuously lit for long periods of time, a laminate useful for producing the same, and a method for producing the laminate. [Brief description of the drawings]
[0018] [Figure 1] Top view of the LED mounting component. [Diagram 2] Cross-sectional view of the LED mounting component. [Diagram 3] FIG. [Figure 4] FIG. 4 is a cross-sectional view of an LED mounting member having a coating film of a first photosensitive resin composition formed thereon. [Diagram 5] FIG. 4 is a cross-sectional view of a state in which a coating film of a first photosensitive resin composition on an LED mounting member has been exposed to light. [Figure 6] 4 is a cross-sectional view of the state after unnecessary portions of the coating film of the first photosensitive resin composition on the LED mounting member have been developed. FIG. [Figure 7] FIG. 2 is a cross-sectional view of a state in which a coating film of a photosensitive resin composition on an LED mounting member is heated after development to form a first organic layer. [Figure 8] FIG. 4 is a cross-sectional view showing a state in which a coating film of a second photosensitive resin composition is formed on the LED mounting member on which the first organic layer is formed. [Figure 9] FIG. 4 is a cross-sectional view of an LED mounting member having a first organic layer and a coating film of a second photosensitive resin composition exposed to light. [Figure 10] FIG. 11 is a cross-sectional view of the state after unnecessary portions of the coating film of the second photosensitive resin composition on the LED mounting member on which the first organic layer is formed have been developed. [Figure 11] FIG. 2 is a top view of a substrate having a conductive layer. [Figure 12]FIG. 2 is a top view of a substrate having bumps and a conductive layer. [Figure 13] Top view of the gripping substrate on which the LEDs are arranged. [Figure 14] Top view of the LED mounting component. [Figure 15] FIG. 4 is a top view of the LED mounting member on which the first organic layer is formed. [Figure 16] FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The laminate of the present invention has a support, a conductive layer, a plurality of light-emitting diodes arranged two-dimensionally, a first organic layer, and a second organic layer.
[0020] The intermediate member of the laminate of the present invention, which has a support, a conductive layer, and a plurality of light-emitting diodes arranged two-dimensionally, is called an LED mounting member. The LED mounting member of the present invention is, for example, a member as shown in Figures 1 and 2. Figure 1 is a top view of the LED mounting member, and Figure 2 is a cross-sectional view taken along line A-A' in Figure 1.
[0021] The laminate of the present invention has a support 1. Examples of the support 1 include a glass substrate, a resin substrate, and a resin film. The material of the glass substrate is preferably non-alkali glass. The material of the resin plate and the resin film is preferably polyester, (meth)acrylic polymer, transparent polyimide, polyethersulfone, and the like. The thickness of the glass plate and the resin plate is preferably 1 mm or less, more preferably 0.8 mm or less. The thickness of the resin film is preferably 100 μm or less.
[0022] The laminate of the present invention has a conductive layer 2. By supplying power to the light-emitting diode 3 via the conductive layer 2, the light-emitting diode 3 can be made to emit light. The material of the conductive layer 2 is preferably a metal or a metal oxide. The metal is preferably any one of gold, silver, copper, aluminum, titanium, and molybdenum. The metal oxide is preferably any one of ITO and IGZO.
[0023] The laminate of the present invention has a plurality of light-emitting diodes 3 arranged two-dimensionally. By arranging the highly durable and highly luminous efficiency light-emitting diodes 3 two-dimensionally and causing them to emit light, a display having excellent characteristics such as high brightness and low power consumption can be produced. The light-emitting diodes 3 are preferably either GaN-based or GaAlInP-based.
[0024] In addition, since Figures 1 and 2 show an LED mounting component in which the conductive layer is formed as a single layer, the two light-emitting diodes 3 lined up vertically in the figures cannot be individually lit. However, it is preferable to form multiple conductive layers via an insulating layer to form a passive matrix system, or to form a conductive layer on a substrate having thin-film transistors (TFTs) to form an active matrix system, so that each light-emitting diode 3 can be individually lit.
[0025] In the LED mounting member, the conductive layer 2 and the LED electrodes 4 of the light-emitting diodes 3 are preferably bonded via bumps 5. By bonding via bumps 5, it is possible to bond a large number of light-emitting diodes 3 to the conductive layer 2 relatively easily even if the thickness of the light-emitting diodes 3 varies.
[0026] The laminate of the present invention has a first organic layer 6. The first organic layer 6 contains (A) a white pigment and (B) a siloxane resin containing at least 10 to 90 mol % in total of repeating units represented by the following general formula (1):
[0027] [ka]
[0028] (R 1 represents an aryl group having 6 to 18 carbon atoms or an aryl group having 6 to 18 carbon atoms in which all or a portion of the hydrogen atoms have been substituted. The first organic layer 6 contains (A) a white pigment, which improves the brightness and reliability of the display. The brightness is thought to be due to the first organic layer 6 being present in the form of a partition in the lateral direction of the chip, which reflects the light emitted from the LEDs in the lateral direction of the chip and guides it toward the front of the display by the white pigment. The principle behind the improvement in reliability is not clear, but it is thought that the inclusion of white pigment particles suppresses the penetration of external gases and other substances, thereby suppressing deterioration of the joints during reliability tests. It is also thought that the inclusion of a white pigment brings physical properties such as the thermal expansion coefficient closer to those of the light-emitting diode 3 and the joints, improving compatibility.
[0029] Examples of white pigments include titanium dioxide, magnesium oxide, barium sulfate, zirconium oxide, zinc oxide, and white lead. Two or more of these may be contained. Among these, it is preferable to contain at least one of titanium dioxide, zirconium oxide, zinc oxide, barium sulfate, and composite compounds thereof, and titanium dioxide, which has high reflectance and is easy to use industrially, is more preferable.
[0030] The crystal structure of titanium dioxide is classified into anatase type, rutile type, and brookite type. Among these, rutile type titanium dioxide is preferred because of its low photocatalytic activity.
[0031] Furthermore, the first organic layer 6 contains (B) a siloxane resin containing at least 10 to 90 mol % in total of repeating units represented by the following general formula (1), and in combination with the second organic layer 7 described below, the reliability of the display is improved. When the repeating units represented by formula (1) are less than 10 mol % or more than 90 mol %, the reliability is reduced. It is preferable that the repeating units represented by formula (1) are contained in a total of 15 to 70 mol %.
[0032] The laminate of the present invention has a second organic layer 7, and the first organic layer 6 and the second organic layer 7 are in contact with each other, and the second organic layer 7 is a transparent layer that does not substantially contain a siloxane resin. In addition, it is preferable that the second organic layer 7 contains any one of an acrylic resin, a cardo resin, a polyimide resin, and a PBO resin, or a mixture thereof. This improves the reliability of the display. Although the principle behind this is not clear, it is considered that the siloxane resin of the first organic layer 6 and the non-siloxane resin of the second organic layer 7 inhibit the penetration of different components, thereby suppressing deterioration of the joint in a reliability test. Here, "substantially does not contain a siloxane resin" means that the siloxane resin content of the second organic layer 7 is 1% by weight or less. In addition, "transparent layer" means that the transmittance at a wavelength of 550 nm per 3 μm of film thickness is 80% or more. Since the second organic layer 7 is a transparent layer, the absorption of light emitted from the light emitting diode 3 can be suppressed, and the brightness of the display is improved.
[0033] In the laminate of the present invention, the thickness of the light-emitting diode 3 is preferably 1 to 20 μm. Generally, a light-emitting diode 3 having a thickness of 20 μm or less is very small and is therefore prone to a decrease in reliability, but the configuration of the laminate of the present invention can prevent such a decrease in reliability. When the thickness is 1 μm or more, the strength of the light-emitting diode is sufficient, and the yield in the mounting process and the like can be improved.
[0034] In the laminate of the present invention, the thickness of the first organic layer 6 is preferably 1 to 20 μm. When the thickness of the first organic layer 6 is 1 μm or more, it is difficult to be affected by the penetration of external gases and the like, and reliability can be improved. When the thickness of the first organic layer 6 is 20 μm or less, the number of reflections and scattering of light emitted from the light emitting diode 3 does not become too large, and a decrease in brightness can be prevented.
[0035] The display of the present invention has the laminate of the present invention. This makes it possible to provide a display with high brightness and high reliability. The display of the present invention may further have, on the laminate of the present invention, a light-shielding layer for improving contrast, an antireflection layer for preventing reflection of external light, a hard coat layer for surface protection, or the like.
[0036] The method for producing a display of the present invention is a method for producing a laminate having a support, a conductive layer, a plurality of light-emitting diodes arranged two-dimensionally, a first organic layer, and a second organic layer, the method comprising the steps of: (I) applying a first photosensitive resin composition to form a first coating film; (II) exposing and developing the first coating; (III) a step of heating the first coating film after the development to form a first organic layer; (IV) applying a second photosensitive resin composition onto the first organic layer to form a second coating film; (V) exposing and developing the second coating; and (VI) heating the developed second coating film to form a second organic layer; These steps allow microfabrication of the first organic layer obtained by curing the first coating film, and the second organic layer obtained by curing the second coating film. By microfabrication of the first organic layer, light emitted from the light-emitting diode 3 can be guided in an appropriate direction, improving the brightness of the display. In addition, these steps allow openings to be formed at the same positions in both the first organic layer and the second organic layer, thereby forming holes penetrating to the support side, and through these holes, it becomes possible to form electrodes that are conductive to the upper layers of the first organic layer and the second organic layer, making it possible to design displays as required, such as forming a touch panel on the upper layer.
[0037] In the present invention, it is preferable to microfabricate the second organic layer 7 and form an opening above the light-emitting diode 3. Although the second organic layer 7 is a transparent layer, it has some light absorption, and therefore, by forming an opening above the light-emitting diode 3, the absorption of light is reduced and the luminance is increased.
[0038] In the present invention, the photosensitive resin composition refers to a material whose solubility in a developer changes due to the action of light.
[0039] In the method for producing a display of the present invention, the first photosensitive resin composition contains (A) a white pigment and (B) a siloxane resin containing a total of 10 to 90 mol % of repeating units represented by at least the following general formula (1):
[0040] [ka]
[0041] (R 1 represents an aryl group having 6 to 18 carbon atoms, or an aryl group having 6 to 18 carbon atoms in which all or a portion of the hydrogen atoms have been substituted.) As a result, the first organic layer contains (A) a white pigment, and (B) a siloxane resin containing at least 10 to 90 mol % in total of repeating units represented by general formula (1), making it possible to produce a display that has high brightness and reliability.
[0042] The siloxane resin is a hydrolysis / dehydration condensation product of organosilane, and in the present invention, contains 10 to 90 mol % in total of the repeating unit represented by the formula (1), and preferably contains 15 to 70 mol % in total of the repeating unit represented by the general formula (1).
[0043] The content ratio of the organosilane unit containing the repeating unit represented by formula (1) is 29 It can be determined by carrying out Si-NMR measurement and calculating the ratio of the integral value of Si originating from organosilane units having the repeating unit represented by formula (1) to the integral value of the entire Si originating from the organosilane.
[0044] The repeating unit represented by the above general formula (1) is derived from an alkoxysilane compound represented by the following general formula (2).
[0045] [ka]
[0046] In the above general formula (2), R 1 R in general formula (1) 1 , which represents the same group as R 2 may be the same or different and represent a monovalent organic group having 1 to 20 carbon atoms, and preferably an alkyl group having 1 to 6 carbon atoms.
[0047] Examples of the organosilane compound represented by the general formula (1) include phenyltrimethoxysilane, phenyltriethoxysilane, phenyltrippropoxysilane, naphthyltrimethoxysilane, naphthyltriethoxysilane, naphthyltrippropoxysilane, styryltrimethoxysilane, etc. Two or more of these may be used.
[0048] The display manufacturing method of the present invention is characterized in that the second photosensitive resin composition does not substantially contain a siloxane resin. In addition, the second photosensitive resin composition preferably contains any one of an acrylic resin, a cardo resin, a polyimide resin, a polyimide precursor resin, and a PBO resin, or a mixture thereof. Here, "substantially does not contain a siloxane resin" means that the siloxane resin content of the second photosensitive resin composition is 1% by weight or less of the solid content. This means that the second organic layer does not substantially contain a siloxane resin, and a highly reliable display can be manufactured.
[0049] The display manufacturing method of the present invention is characterized in that the second photosensitive resin composition is a resin composition for forming a transparent layer. The term "transparent layer-forming resin composition" refers to a composition in which the transmittance of the coating film at a wavelength of 550 nm is 80% or more after at least coating, developing, and heating the photosensitive resin composition so as to form an organic layer with a thickness of 3 μm. This allows the second organic layer to be a transparent layer, suppresses absorption of light emitted from the light-emitting diode 3, and increases the brightness of the display.
[0050] The first photosensitive resin composition and the second photosensitive resin composition may each be either a negative photosensitive resin composition in which the light irradiated portion is insoluble in a developer, or a positive photosensitive resin composition in which the light irradiated portion is soluble in a developer.
[0051] In the present invention, the bumps can be formed by known methods, such as a method of forming a pattern of a metal such as gold, tin, indium, or an alloy thereof on a conductive layer by a method such as photolithography, or a method of patterning using a photosensitive conductive paste, which is a photosensitive resin composition having conductivity. EXAMPLES
[0052] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. Among the compounds used in the synthesis examples and examples, the abbreviations are shown below. PGMEA: Propylene glycol monomethyl ether acetate DAA: Diacetone alcohol NMP: N-methyl-2-pyrrolidone.
[0053] The solid content concentration of the resin solution in Synthesis Examples 1 to 3 and 6 was determined by the following method. 1.5 g of the resin solution was weighed out in an aluminum cup and heated at 250° C. for 30 minutes using a hot plate to evaporate the liquid. The weight of the solid content remaining in the aluminum cup after heating was weighed, and the solid content concentration of the resin solution was determined from the ratio to the weight before heating.
[0054] The weight average molecular weight of the resin in Synthesis Examples 1 to 3 was determined by the following method. Using a GPC analyzer (HLC-8220; manufactured by Tosoh Corporation) and tetrahydrofuran as a fluidized bed, GPC analysis was performed based on "JIS K 7252-3 (established on March 20, 2008)" to measure the weight average molecular weight in terms of polystyrene.
[0055] The content ratio of each organosilane unit in the polysiloxane in Synthesis Examples 1 and 2 was determined by the following method. The polysiloxane solution was poured into a 10 mm diameter Teflon (registered trademark) NMR sample tube. 29 Si-NMR measurement was performed, and the content ratio of each organosilane unit was calculated from the ratio of the integral value of Si derived from a specific organosilane unit to the integral value of the entire Si derived from the organosilane. 29 The Si-NMR measurement conditions are as follows. Equipment: Nuclear magnetic resonance apparatus (JNM-GX270; manufactured by JEOL Ltd.) Measurement method: Gated decoupling method Measured nuclear frequency: 53.6693MHz ( 29 Si nucleus) Spectral width: 20000Hz Pulse width: 12μs (45° pulse) Pulse repetition time: 30.0 seconds Solvent: Acetone-d6 Reference material: Tetramethylsilane Measurement temperature: 23℃ Sample rotation speed: 0.0Hz.
[0056] Synthesis Example 1 Siloxane negative resin (SN-1) solution In a 1000 mL three-neck flask, 71.16 g (0.306 mol) of 3-methacryloxypropylmethyldimethoxysilane, 78.52 g (0.35 mol) of styryltrimethoxysilane, 21.56 g (0.088 mol) of 3-(3,4-epoxycyclohexyl)propyltrimethoxysilane, 113.22 g (0.83 mol) of methyltrimethoxysilane, 45.91 g (0.175 mol) of 3-trimethoxysilylpropylsuccinic anhydride, 1.080 g of dibutylhydroxytoluene, and 234.92 g of PGMEA were charged, and an aqueous phosphoric acid solution in which 3.304 g of phosphoric acid (1.0 wt % relative to the charged monomer) was dissolved in 92.14 g of water was added over 30 minutes while stirring at 40°C. After that, the flask was immersed in a 70°C oil bath and stirred for 60 minutes, and the oil bath was heated to 115°C over 30 minutes. One hour after the start of the temperature increase, the solution temperature (internal temperature) reached 100°C, and the mixture was heated and stirred for 2 hours (internal temperature was 100-110°C) to obtain a polysiloxane solution. During the temperature increase and heating and stirring, a mixed gas of 95% by volume of nitrogen and 5% by volume of oxygen was flowed at 0.05 liters / minute. A total of 209 g of methanol and water, which are by-products, was distilled during the reaction. PGMEA was added to the obtained polysiloxane solution so that the solid concentration was 40% by weight, and a siloxane negative resin (SN-1) solution was obtained. The weight average molecular weight of the obtained siloxane negative resin (SN-1) was 12,000. In addition, the molar ratios of the repeating units derived from 3-methacryloxypropylmethyldimethoxysilane, styryltrimethoxysilane, 3-(3,4-epoxycyclohexyl)propyltrimethoxysilane, methyltrimethoxysilane, and 3-trimethoxysilylpropylsuccinic anhydride in the siloxane negative resin (SN-1) were 17.5 mol%, 20 mol%, 5 mol%, 47.5 mol%, and 10 mol%, respectively. That is, the content of the repeating unit represented by the general formula (1) was 20%.
[0057] Synthesis Example 2 Siloxane positive resin (SP-1) solution In a 500mL three-neck flask, 99.15g (0.500mol) of phenyltrimethoxysilane, 24.64g (0.100mol) of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 54.48g (0.400mol) of methyltrimethoxysilane, and 103.44g of PGMEA were charged, and while stirring at room temperature, an aqueous phosphoric acid solution in which 0.768g of phosphoric acid (0.50% by weight relative to the charged monomer) was dissolved in 54.00g of water was added over 30 minutes. After that, the three-neck flask was immersed in a 70°C oil bath and stirred for 90 minutes, and the oil bath was heated to 115°C over 30 minutes. One hour after the start of the temperature increase, the internal temperature (solution temperature) of the three-neck flask reached 100°C, and the mixture was heated and stirred for 2 hours (internal temperature was 100-110°C) to obtain a polysiloxane solution. During the temperature increase and heating and stirring, nitrogen was flowed at 0.05 liters / minute. During the reaction, a total of 123.00 g of by-products, methanol and water, was distilled off. PGMEA was added to the obtained polysiloxane solution so that the solids concentration was 40% by weight, and a siloxane positive resin (SP-1) solution was obtained. The weight average molecular weight of the obtained siloxane positive resin (SP-1) was 4,100 (polystyrene equivalent). In addition, 29 From the Si-NMR measurement results, the molar ratios of the repeating units derived from phenyltrimethoxysilane, 3-(3,4-epoxycyclohexyl)propyltrimethoxysilane, and methyltrimethoxysilane in the siloxane positive resin (SP-1) were 50 mol%, 10 mol%, and 40 mol%, respectively. That is, the content of the repeating unit represented by the general formula (1) was 50%.
[0058] Synthesis Example 3 Acrylic negative resin (AN-1) solution In a 500mL three-neck flask, 3g of 2,2'-azobis(isobutyronitrile) and 50g of PGMEA were charged. Then, 30g of methacrylic acid, 35g of benzyl methacrylate, and 35g of tricyclo[5.2.1.02,6]decan-8-yl methacrylate were charged, stirred at room temperature for a while, and the atmosphere in the flask was replaced with nitrogen. Then, heated and stirred at 70°C for 5 hours to obtain an acrylic resin solution. PGMEA was added to the obtained acrylic resin solution so that the solid concentration was 40% by weight, and an acrylic negative resin (AN-1) solution was obtained. The weight average molecular weight of the acrylic negative resin (AN-1) was 10,000 (polystyrene equivalent).
[0059] Synthesis Example 4 Hydroxyl-containing diamine compound 18.3g (0.05mol) of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane was dissolved in 100mL of acetone and 17.4g (0.3mol) of propylene oxide, and cooled to -15℃. A solution of 20.4g (0.11mol) of 3-nitrobenzoyl chloride dissolved in 100mL of acetone was added dropwise to the solution. After the addition was completed, the mixture was reacted at -15℃ for 4 hours, and then returned to room temperature. The precipitated white solid was filtered and dried in vacuum at 50℃.
[0060] 30 g of the solid was placed in a 300 mL stainless steel autoclave and dispersed in 250 mL of methyl cellosolve, and 2 g of 5% palladium-carbon was added. Hydrogen was introduced into the autoclave using a balloon, and the reduction reaction was carried out at room temperature. After about 2 hours, the reaction was terminated when it was confirmed that the balloon was no longer deflating. After the reaction was completed, the mixture was filtered to remove the palladium compound catalyst, and the mixture was concentrated using a rotary evaporator to obtain a hydroxyl group-containing diamine compound represented by the following formula (3).
[0061] [ka]
[0062] Synthesis Example 5 Polyimide positive resin (IP-1) Under a dry nitrogen stream, 31.0 g (0.10 mol) of 3,3',4,4'-diphenylethertetracarboxylic dianhydride was dissolved in 500 g of NMP. 45.35 g (0.075 mol) of the hydroxyl group-containing diamine compound obtained in Synthesis Example 5 and 1.24 g (0.005 mol) of 1,3-bis(3-aminopropyl)tetramethyldisiloxane were added together with 50 g of NMP, and the mixture was reacted at 20°C for 1 hour, and then at 50°C for 2 hours. Next, 4.36 g (0.04 mol) of 4-aminophenol was added together with 5 g of NMP as a terminal blocking agent, and the mixture was reacted at 50°C for 2 hours. Then, a solution obtained by diluting 28.6 g (0.24 mol) of N,N-dimethylformamide dimethylacetal with 50 g of NMP was added dropwise over 10 minutes. After the dropwise addition, the mixture was stirred at 50°C for 3 hours. After the stirring was completed, the solution was cooled to room temperature and then poured into 3 L of water to obtain a white precipitate. The precipitate was collected by filtration, washed three times with water, and then dried in a vacuum dryer at 80°C for 24 hours to obtain the desired polyimide precursor, a polyimide positive resin (IP-1).
[0063] Synthesis Example 6 Acrylic positive resin (AP-1) solution 5g of 2,2'-azobis(isobutyronitrile), 5g of t-dodecanethiol, and 150g of PGMEA were added to a 500mL flask. Then, 30g of methacrylic acid, 35g of benzyl methacrylate, and 35g of tricyclo[5.2.1.02,6]decan-8-yl methacrylate were added, stirred at room temperature for a while, and the flask was replaced with nitrogen, and then heated and stirred at 70°C for 5 hours. Next, 15g of glycidyl methacrylate, 1g of dimethylbenzylamine, and 0.2g of p-methoxyphenol were added to the obtained solution, and heated and stirred at 90°C for 4 hours to obtain an acrylic positive resin (AP-1) solution. The solid content concentration of the acrylic positive resin (AP-1) in the obtained solution was 43% by weight.
[0064] Synthesis Example 7 Carboxyl-containing acrylic copolymer having unsaturated double bonds (AN-2) In a reaction vessel in a nitrogen atmosphere, 150g of diethylene glycol monobutyl ether (hereinafter, "DGME") was charged and heated to 80°C using an oil bath. A mixture consisting of 20g of ethyl acrylate (hereinafter, EA), 40g of 2-ethylhexyl methacrylate (hereinafter, 2-EHMA), 20g of n-butyl acrylate (hereinafter, BA), 15g of N-methylol acrylamide (hereinafter, MAA), 0.8g of 2,2'-azobisisobutyronitrile and 10g of DGME was added dropwise over 1 hour. After the dropwise addition was completed, the mixture was heated at 80°C for another 6 hours to carry out a polymerization reaction. Then, 1g of hydroquinone monomethyl ether was added to stop the polymerization reaction. Subsequently, a mixture consisting of 5g of glycidyl methacrylate (hereinafter, GMA), 1g of triethylbenzylammonium chloride and 10g of DGME was added dropwise over 0.5 hours. After the dropwise addition was completed, the mixture was heated for an additional 2 hours to carry out the addition reaction. The resulting reaction solution was purified with methanol to remove unreacted impurities, and then vacuum dried for 24 hours to obtain a carboxyl-containing acrylic copolymer (J) having an unsaturated double bond with a copolymerization ratio (by mass): EA / 2-EHMA / BA / GMA / AA=20 / 40 / 20 / 5 / 15.
[0065] Synthesis Example 8 Quinone diazide compound (QD-1) Under a dry nitrogen stream, 21.22 g (0.05 mol) of TrisP-PA (trade name, manufactured by Honshu Chemical Industry Co., Ltd.) and 36.27 g (0.135 mol) of 5-naphthoquinone diazide sulfonyl chloride were dissolved in 450 g of 1,4-dioxane and brought to room temperature. 15.18 g of triethylamine mixed with 50 g of 1,4-dioxane was added dropwise so that the temperature in the system did not exceed 35°C. After the addition, the mixture was stirred at 30°C for 2 hours. The triethylamine salt was filtered, and the filtrate was poured into water. The precipitate was then collected by filtration. The precipitate was dried in a vacuum dryer to obtain a quinone diazide compound (QD-1) represented by the following formula.
[0066] Preparation Example 1 Siloxane negative white material (SNW-1) resin composition 5.00 g of titanium dioxide pigment (R-960; manufactured by BASF Japan Ltd. (hereinafter, R-960)) as a white pigment and 5.00 g of the siloxane negative resin (SN-1) solution obtained in Synthesis Example 1 as a resin were mixed and dispersed using a mill-type disperser filled with zirconia beads to obtain a pigment dispersion.
[0067] Next, 8.25 g of the pigment dispersion, 7.025 g of siloxane negative resin (SN-1) solution, 0.155 g of ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime) ("Irgacure" (registered trademark) OXE-02, manufactured by BASF Japan Ltd. (hereinafter, OXE-02)) as a photopolymerization initiator, 0.258 g of bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide ("Irgacure" 819, manufactured by BASF Japan Ltd. (hereinafter, IC-819)) as a photopolymerizable compound, and dipentaerythritol hexaacrylate ("KAYARAD" (registered trademark) DPHA, manufactured by Shin Nippon Pharmaceutical Co., Ltd.) as a photopolymerizable compound were mixed. 2.063 g of 3',4'-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate ("Celloxide" (registered trademark) 2021P, Daicel Corporation), 0.021 g of ethylene bis(oxyethylene) bis[3-(5-tert-butyl-4-hydroxy-m-tolyl)propionate] ("Irganox" (registered trademark) 1010, BASF Japan Co., Ltd.), and 0.103 g of a 10 wt% diluted solution of acrylic surfactant ("BYK" (registered trademark) 352, BYK Japan Co., Ltd.) in PGMEA (corresponding to a concentration of 500 ppm) were dissolved in 2.72 g of solvent PGMEA and stirred. The resulting mixture was filtered through a 5.0 μm filter to obtain a siloxane negative white material (SNW-1) resin composition.
[0068] Preparation Example 2 Acrylic negative white material (ANW-1) resin composition An acrylic negative white material (ANW-1) resin composition was obtained in the same manner as in Preparation Example 1, except that the acrylic negative resin (AN-1) solution was used instead of the siloxane positive resin (SP-1) solution.
[0069] Preparation Example 3 Siloxane positive white material (SPW-1) resin composition (A) 50.00 g of R-960 as a white pigment and 50.00 g of a solution of the siloxane positive resin (SP-1) obtained in Synthesis Example 2 as a resin were mixed and dispersed using a mill-type disperser filled with zirconia beads to obtain a pigment dispersion.
[0070] Next, 32.00 g of the pigment dispersion, 34.925 g of the siloxane positive resin (SP-1) solution, 2.000 g of TP5-280M (manufactured by Toyo Gosei Co., Ltd.) as a (G) naphthoquinone dope compound, 0.800 g of a melamine resin compound ("Nicalac" (registered trademark) MX-270 (trade name), manufactured by Sanwa Kasei Co., Ltd.) as a curing agent, 0.800 g of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (KBM-303 (trade name), manufactured by Shin-Etsu Chemical Co., Ltd.) as an adhesion improver, and 0.300 g (corresponding to a concentration of 300 ppm) of a 10 wt % PGMEA diluted solution of a fluorine-based surfactant ("Megafac" (registered trademark) F-477 (trade name), manufactured by DIC Corporation) as a surfactant were dissolved in a mixed solvent of 3.000 g of DAA and 26.175 g of PGMEA, and stirred. Next, the mixture was filtered through a 5.0 μm filter to obtain a siloxane positive white material (SPW-1) resin composition.
[0071] Preparation Example 4 Polyimide positive transparent material (IPT-1) resin composition 10.0 g of the polyimide positive resin (IP-1) obtained in Synthesis Example 5, 2.0 g of the quinone diazide compound (QD-1) obtained in Synthesis Example 7, and 2.0 g of NC3000 (trade name, manufactured by Nippon Kayaku Co., Ltd.) as a thermal crosslinking agent, which is an epoxy compound, were dissolved in 30.0 g of propylene glycol monomethyl ether and 8.0 g of γ-butyrolactone as an organic solvent, and then the solution was filtered through a 0.2 μm polytetrafluoroethylene filter (manufactured by Sumitomo Electric Industries, Ltd.) to obtain a polyimide positive transparent material (IPT-1) resin composition.
[0072] Preparation Example 5 Acrylic positive transparent material (APT-1) resin composition 23.3 g of the acrylic positive resin (AP-1) solution obtained in Synthesis Example 6, 2.0 g of the quinone diazide compound (QD-1) obtained in Synthesis Example 7, and 2.0 g of NC3000 were dissolved in 16.7 g of propylene glycol monomethyl ether and 8.0 g of γ-butyrolactone as organic solvents, and then filtered through a 0.2 μm polytetrafluoroethylene filter (manufactured by Sumitomo Electric Industries, Ltd.) to obtain an acrylic positive transparent material (APT-1) resin composition.
[0073] Preparation Example 6 Siloxane positive transparent material (SPT-1) resin composition Siloxane resin (SP-1) solution 12.338 g, (C) naphthoquinone dihydrogen compound TP5-280M (manufactured by Toyo Gosei Co., Ltd.) 1.000 g, curing agent CGI-MDT (manufactured by Hereus Co., Ltd.) 0.150 g, melamine resin compound ("Nicalac" (registered trademark) MX-270 (trade name), Sanwa Kasei Co., Ltd.) 0.200 g, adhesion improver 3-glycidoxypropanol 0.200 g of pyrmethyldimethoxysilane (KBM-303 (trade name), Shin-Etsu Chemical Co., Ltd.) and 1.500 g (corresponding to a concentration of 300 ppm) of a 1 wt % PGMEA diluted solution of a fluorine-based surfactant ("Megafac" (registered trademark) F-477 (trade name), DIC Corporation) as a surfactant were dissolved in a mixed solvent of 8.000 g of DAA and 21.613 g of PGMEA and stirred. Next, the mixture was filtered through a 5.0 μm filter to obtain a siloxane positive transparent material (SPT-1) resin composition.
[0074] Preparation Example 7 Photosensitive conductive paste (ANC-1) Into a 100 mL clean bottle were placed 15.00 g of a carboxyl group-containing acrylic copolymer having an unsaturated double bond (AN-2), 0.66 g of a photopolymerization initiator ("IRGACURE" (registered trademark) OXE04 (trade name), manufactured by BASF Japan Ltd.), 1.5 g of a compound having an unsaturated double bond ("Light Acrylate" (registered trademark) BP-4EA (trade name), manufactured by Kyoeisha Chemical Co., Ltd.), 3.82 g of an epoxy resin ("EPICLON" (registered trademark) 840 (trade name), manufactured by DIC Corporation), 2.17 g of a novolak phenolic resin H-4 (trade name, manufactured by Meiwa Kasei Co., Ltd.), and 5.78 g of DGME, and mixed using a rotation-revolution vacuum mixer "Awatori Rentaro" (registered trademark) ARE-310 (manufactured by Thinky Corporation) to obtain 28.94 g of a resin solution.
[0075] The resulting resin solution (28.94 g) was mixed with 54.02 g of Ag particles with a particle size (D50) of 0.5 μm and an aspect ratio of 1.1, and kneaded using a three-roller mill (EXAKT M-50; manufactured by EXAKT) to obtain 82.96 g of a photosensitive conductive paste (ANC-1). <Preparation of a substrate having bumps and a conductive layer> On a glass substrate, gold was patterned as a conductive layer in the shape shown in Fig. 11. In Fig. 11, conductive layer protrusions 15, which are the locations for bonding flip-chip type LEDs, were formed with a vertical spacing of L1 = 200 μm, 50 in number in the vertical direction, a horizontal spacing of L1 = 200 μm, and 50 in number in the horizontal direction.
[0076] A photosensitive conductive paste (ANC-1) was screen-printed on the substrate having the conductive layer described above, and then heated in a drying oven at 100° C. for 5 minutes. After that, a direct writing exposure device (MX-1201; manufactured by Dainihon Kaken Co., Ltd.) was used to apply an exposure dose of 300 mJ / cm, taking into account the amount of line thickening in the exposed area. 2 (Equivalent to a wavelength of 375 nm) was used to expose 5,000 bumps with a film thickness of 3 μm and a size of 12 × 11 μm so that the distance between each pair of bumps was 14 μm.
[0077] After exposure, spray development was carried out for 20 seconds using a 0.1 wt% aqueous Na2CO3 solution, followed by rinsing with ultrapure water to obtain a substrate having bumps and a conductive layer in the shape of FIG. 12. <Fabrication of LED Mounting Member> An adhesive layer (KR-3704, manufactured by Shin-Etsu Chemical Co., Ltd.) with a film thickness of 5 μm was formed on a silicon wafer cut into 30 mm × 30 mm to obtain a gripping substrate.
[0078] On the gripping substrate, a flip-chip type light-emitting diode with a size of 18 × 36 μm was arranged in a matrix of 50 rows and 50 columns with a pitch of 200 μm such that the LED electrodes faced upward to fabricate the substrate of FIG. 13.
[0079] Using a flip-chip bonder (FC-3000WS, manufactured by Toray Engineering Co., Ltd.), the substrate having bumps and a conductive layer was fixed to the stage, the gripping substrate on which the electronic components were arranged was picked up, the LED electrodes on the gripping substrate were opposed to the conductive resin bumps of the substrate having bumps and a conductive layer, and thermocompression bonding was performed under the conditions of a stage temperature of 40°C, a head temperature of 120°C, a load of 25 N, and 60 seconds, and then the gripping substrate was peeled off. By this process, the LED mounting member of FIG. 14 was fabricated. <Transmittance Evaluation> For an organic layer with a film thickness of 3 μm formed on a non-alkali glass substrate, the transmittance at 550 nm was measured using a spectrophotometer U-4100 (manufactured by Hitachi, Ltd.) with the transmittance of the non-alkali glass substrate without the organic layer formed as the baseline. <Luminance Evaluation> A voltage of 3.0 V was applied between the electrodes at the upper and lower ends of the substrate of the laminate, and the luminance was measured using a spectro-radiance meter (CS-1000, manufactured by Konica Minolta Inc.). When the luminance of Example 1 was set to 100, cases where the relative luminance was 95 or more were rated as A, 90 or more and less than 95 were rated as B, 80 or more and less than 90 were rated as C, and less than 80 were rated as E. E indicates low luminance and is unsuitable. <Reliability Evaluation> A voltage of 3.0V was applied between the electrodes at the top and bottom of the board, and after 500 hours of continuous lighting, if 0 to 1 out of 2,500 LEDs became unlit, it was rated A, if 2 to 4 LEDs became unlit, it was rated B, if 5 to 10 LEDs became unlit, it was rated C, and if more than that, it was rated E. Grade E is unsuitable for low reliability. Example 1 A siloxane negative white material (SNW-1) resin composition was spin-coated on an LED mounting member under conditions that would result in a film thickness of 5 μm after a process of obtaining a first organic layer by heating, and then dried at a temperature of 100° C. for 3 minutes using a hot plate (product name SCW-636, manufactured by Dainippon Screen Mfg. Co., Ltd.) to produce a coating film. The coating film thus produced was then aligned using a parallel light mask aligner (product name PLA-501F, manufactured by Canon Inc.) with an ultra-high pressure mercury lamp as the light source, through a photomask with an exposure dose of 300 mJ / cm 2 in a 20×40 μm area whose center coincides with the LED on the LED mounting member and with the electrode parts at the top and bottom ends as light-shielding parts. 2 The film was exposed to 10000 x 1000 nm (g, h, i rays). It was then shower-developed for 100 seconds using an automatic developing device (Takizawa Sangyo Co., Ltd.'s "AD-2000 (product name)") with a 0.045 wt % potassium hydroxide aqueous solution, and then rinsed with water for 30 seconds. It was then heated in air at a temperature of 180°C for 30 minutes using an oven (product name IHPS-222, Espec Corp.) to obtain an LED mounting member with the first organic layer of FIG. 15 formed.
[0080] Next, an acrylic positive transparent material (APT-1) resin composition was spin-coated on the LED mounting member on which the first organic layer was formed under conditions such that the film thickness on the first organic layer would be 3 μm after the step of heating to obtain a second organic layer, and then dried at a temperature of 120° C. for 2 minutes using a hot plate (product name SCW-636, manufactured by Dainippon Screen Mfg. Co., Ltd.) to produce a coating film. The produced coating film was then irradiated with light using a parallel light mask aligner (product name PLA-501F, manufactured by Canon Inc.) with an ultra-high pressure mercury lamp as the light source, through a photomask with an area of 30×15 μm whose center coincides with the LED on the LED mounting member and with the electrode parts at the upper and lower ends as light-transmitting parts, at an exposure dose of 600 mJ / cm. 2The film was exposed to 1000 nm (g, h, i rays). It was then developed using an automatic developing device (Takizawa Sangyo Co., Ltd.'s "AD-2000 (product name)") with a 2.38% by weight aqueous solution of tetramethylammonium, and only the exposed areas were dissolved, followed by rinsing with pure water. It was then cured in an oven at 250°C for 60 minutes under a nitrogen atmosphere to obtain the laminate shown in FIG. 16.
[0081] Under the same conditions as those of the second organic layer formation process, an acrylic positive transparent material (APT-1) resin composition was spin-coated on an alkali-free glass substrate, dried, developed, and cured to form a 3 μm-thick organic layer. The organic layer had a transmittance of 94%, and was a transparent layer.
[0082] The resulting laminate had a brightness of A and a reliability of A. Example 2 In Example 1, a siloxane positive white material (SPW-1) resin composition was used instead of the siloxane negative white material (SNW-1) resin composition in the first organic layer formation step, and a photomask having a light-transmitting portion in a 40 × 20 μm range whose center coincides with the LED on the LED mounting member and in the range of the electrode portions at the upper and lower ends was used, and an exposure dose of 500 mJ / cm was obtained. 2 A laminate was obtained in the same manner as in Example 1, except that the exposure was performed at 400 nm.
[0083] The resulting laminate had a brightness of A and a reliability of A. Example 3 In Example 1, a polyimide positive transparent material (IPT-1) resin composition was used instead of the acrylic positive transparent material (APT-1) resin composition in the second organic layer formation step, and the exposure dose was 200 mJ / cm 2 A laminate was obtained in the same manner as in Example 1, except that the exposure was performed at 400 nm.
[0084] Under the same conditions as those of the second organic layer formation process, a polyimide positive transparent material (IPT-1) resin composition was spin-coated on an alkali-free glass substrate, dried, developed, and cured to form a 3 μm-thick organic layer. The organic layer had a transmittance of 88%, and was a transparent layer.
[0085] The resulting laminate had a brightness of A and a reliability of A. Example 4 A laminate was obtained in the same manner as in Example 1, except that exposure was performed through a photomask in which a light-transmitting portion was provided only in the range of the electrode portions at the upper and lower ends, as the photomask in the second organic layer formation step.
[0086] The luminance of the obtained laminate was rated B, and the reliability was rated A. The slight decrease in luminance is believed to be due to the increased light absorption of the second organic layer compared to the case where an opening is formed over the LED. Example 5 A laminate was obtained in the same manner as in Example 3, except that in the second organic layer forming step, exposure was performed through a photomask having a light-transmitting portion only in the range of the electrode portions at the upper and lower ends.
[0087] The brightness of the obtained laminate was C, and the reliability was A. The slight decrease in brightness is considered to be due to the increased light absorption of the second organic layer compared to the case where an opening is formed over the LED. Comparative Example 1 In Example 1, the step of forming the second organic layer was omitted.
[0088] The luminance of the obtained laminate was rated A, and the reliability was rated E, both of which were unsuitable. Comparative Example 2 In Example 1, a siloxane positive transparent material (SPT-1) resin composition was used instead of the acrylic positive transparent material (APT-1) resin composition in the second organic layer formation step, and the exposure dose was 200 mJ / cm 2 A laminate was obtained in the same manner as in Example 1, except that the exposure was performed at 400 nm.
[0089] Under the same conditions as those of the second organic layer formation process, a siloxane positive white material (SPW-1) resin composition was spin-coated on an alkali-free glass substrate, dried, developed, and cured to form an organic layer having a thickness of 3 μm. The organic layer had a transmittance of 98% and was a transparent layer.
[0090] The luminance of the obtained laminate was rated A, and the reliability was rated E, both of which were unsuitable. Comparative Example 3 In Example 2, a siloxane positive transparent material (SPT-1) resin composition was used instead of the acrylic positive transparent material (APT-1) resin composition in the second organic layer formation step, and the exposure dose was 200 mJ / cm 2 A laminate was obtained in the same manner as in Example 1, except that the exposure was performed at 400 nm.
[0091] The luminance of the obtained laminate was rated A, and the reliability was rated E, both of which were unsuitable. Comparative Example 4 A laminate was obtained in the same manner as in Example 1, except that in the first organic layer forming step, an acrylic negative whitening material (ANW-1) resin composition was used instead of the siloxane negative whitening material (SNW-1) resin composition.
[0092] The luminance of the obtained laminate was rated A, and the reliability was rated E, both of which were unsuitable. Comparative Example 5 In Example 2, a siloxane positive transparent material (SPT-1) resin composition was used instead of the siloxane positive white material (SPW-1) resin composition in the first organic layer formation step, and the exposure dose was 200 mJ / cm 2 A laminate was obtained in the same manner as in Example 2, except that exposure was performed with (g, h, i rays).
[0093] The luminance of the obtained laminate was E, and the reliability was C, which means that the luminance was inadequate. This is thought to be because the light emitted from the light-emitting diode toward the side was no longer extracted forward. In addition, the reliability was also thought to have decreased due to the absence of a white pigment.
[0094] [Table 1] [Explanation of symbols]
[0095] 1 Support 2 Conductive layer 3. Light-emitting diode 4 LED electrodes 5. Bump 6 First organic layer 7. Second Organic Layer 8 Coating film of first photosensitive resin composition 9. Photomask 10. Post-exposure coating of first photosensitive resin composition 11. Developed coating film of first photosensitive resin composition 12 Coating film of second photosensitive resin composition 13. Coating film after exposure of the third photosensitive resin composition 14. Coating film after development of the fourth photosensitive resin composition 15 Conductive layer protrusion 16 Gripping board [Industrial Applicability]
[0096] According to the present invention, it is possible to provide a highly reliable micro LED display that is high-brightness and does not fail to light even when continuously lit for a long period of time, a laminate useful for manufacturing the same, and a method for manufacturing the laminate.
Claims
1. A laminate having a support, a conductive layer, a plurality of light-emitting diodes arranged two-dimensionally, a first organic layer, and a second organic layer, the first organic layer and the second organic layer being in contact with each other, the first organic layer containing (A) a white pigment, and (B) a siloxane resin containing at least 10 to 90 mol % in total of a repeating unit represented by the following general formula (1), and the second organic layer being a transparent layer that is substantially free of siloxane resin: 【Chemistry 1】 (R 1 represents an aryl group having 6 to 18 carbon atoms or an aryl group having 6 to 18 carbon atoms in which all or a portion of the hydrogen atoms have been substituted.
2. The laminate of claim 1 , wherein the second organic layer comprises an acrylic resin, a cardo resin, a polyimide resin, a PBO resin, or a mixture thereof.
3. 3. The laminate according to claim 1, wherein the light-emitting diode has a thickness of 1 to 20 μm.
4. 2. The laminate according to claim 1, wherein the first organic layer has a thickness of 1 to 20 μm.
5. The laminate according to claim 1 , wherein the conductive layer is a metal layer and / or a metal oxide layer.
6. A display comprising the laminate according to claim 1.
7. A method for manufacturing a laminate having a support, a conductive layer, a plurality of light-emitting diodes arranged two-dimensionally, a first organic layer, and a second organic layer, the method comprising the steps of: (I) applying a first photosensitive resin composition to form a first coating film; (II) exposing and developing the first coating film; (III) a step of heating the first coating film after the development to form a first organic layer; (IV) applying a second photosensitive resin composition onto the first organic layer to form a second coating film; (V) exposing and developing the second coating; and (VI) a step of heating the developed second coating film to form a second organic layer; Including, The first photosensitive resin composition contains (A) a white pigment and (B) a siloxane resin containing a repeating unit represented by at least the following general formula (1) in a total amount of 10 to 90 mol %, A method for producing a laminate, wherein the second photosensitive resin composition is a transparent layer-forming resin composition that is substantially free of a siloxane resin. 【Chemistry 2】 (R 1 represents an aryl group having 6 to 18 carbon atoms or an aryl group having 6 to 18 carbon atoms in which all or a portion of the hydrogen atoms have been substituted.
Citation Information
Patent Citations
Method for manufacturing cured-film-coated substrate, cured-film-coated substrate, and element comprising cured-film-coated substrate
WO2023054046A1